Artificial Intelligence (AI) dalam Pendidikan Agama Islam: Perspektif Filsafat Sains - Aimmah, Siti Chaulatul; Nabila, Khurin Ain; Lestari, Putri Dwi; Suprayogi, Agus (TSAQOFAH, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to the field of education, including in Pendidikan Agama Islam (PAI), thereby necessitating critical examination to ensure its use remains aligned with the aims of Islamic education. This study aimed to analyze the use of AI in PAI learning from the perspective of the philosophy of science in terms of ontology, epistemology, and axiology in order to understand the position, role, and value implications of this technology. The research employed a qualitative approach with a literature review method based on a systematic literature review (SLR), through the identification and analysis of relevant national and international journal articles, scientific conference proceedings, and academic books published between 2020 and 2025. Data were analyzed using thematic and conceptual–philosophical analysis techniques to identify patterns of findings and the philosophical implications of AI use in PAI learning. The findings show that AI functions as an effective pedagogical tool for enhancing the efficiency, personalization, and accessibility of learning, but it cannot replace the role of the teacher as a moral guide and value educator. Ontologically, AI is understood as a technological artefact devoid of consciousness; epistemologically, the knowledge it generates is data-driven and assistive; and axiologically, the value of AI is determined by the orientation of its use in relation to the aims of Islamic education. This study concludes that the integration of AI in PAI learning must be situated within a human-centered and value-oriented educational framework, thereby offering a theoretical contribution to the development of the philosophy of Islamic education and providing a conceptual foundation for adaptive and meaningful educational practice in the digital era.